Biosourced Polymetallic Catalysis: A Surprising and Efficient Means to Promote the Knoevenagel Condensation - Deyris, Pierre-Alexandre; Bert, Valérie; Diliberto, Sébastien; Boulanger, Clotilde; Petit, Eddy; Legrand, Yves-Marie; Grison, Claude (Frontiers in Chemistry, 2018)
Zn hyperaccumulator (Arabidobsis halleri) and Zn accumulator Salix ‘Tordis’ (Salix schwerinii x S. viminalis) have shown their interest in the phytoextraction of polluted brownfields. Herein, we explore an innovative methodology based on the chemical valorization of Zn-rich biomass produced by these metallophyte plants. The approach is based on the direct use of polymetallic salts derived from plants as “Lewis acid” catalysts in organic chemistry. The formed ecocatalysts were characterized via ICP-MS, XRD, FT-IR in order to elucidate the chemical composition, structure and behavior of the formed materials. The Doebner-Knoevenagel reaction was chosen as model reaction to study their synthetic potential. Significant differences to conventional catalysts such as zinc (II) chloride are observed. They can principally be related to a mixture of unusual mineral species. DFT calculations were carried out on these salts in the context of the Gutmann theory. They allow the rationalization of experimental results. Finally, these new bio-based polymetallic catalysts illustrated the interest of this concept for green and sustainable catalysis.